Analisis Pendapatan Usahatani Jahe Di Desa Mokobang Kecamatan Modoinding Kabupaten Minahasa Selatan - Rorimpandey, Lovenia Regina; Sondakh, Mex Frans Lodwyk; Waney, Nordy F.L. (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the income of ginger farming in Mokobang Village, Modoinding District, South Minahasa Regency. The research was carried out for 2 months from July to August 2022. The sampling method used the purposive sampling method with criteria based on farmers who had harvested during the research, taken farmers who harvested the January-June period and the July-August 2022 period with 15 respondents. farmer. The research uses primary data obtained from direct observation and interviews with respondents using a questionnaire. Secondary data was obtained from related agencies, namely the Agricultural Extension Center (AEC) Modoinding District and the Mokobang Village Government. The analytical method used in this research is income analysis and farming feasibility analysis. The results showed that the average income of ginger farming which was harvested in January-June was IDR 2,515,636/Ha with an average land area of 0.61 Ha, while the income earned by ginger farmers who were harvested in July-August was IDR 3,714,610/ Ha with an average land area of 0.29 Ha for one growing season (9 months). The R/C ratio of ginger farmers who harvest in January-June is 1.10 and the R/C value of ginger farmers who harvest in July-August is 1.09. The R/C value obtained is more than 1, this shows that ginger farming in Mokobang Village is feasible to be cultivated.